Aqueous-only exfoliation of pristine graphite to graphene : towards sustainable, multifunctional polymer nanocomposites - Seyed Ismail Seyed Shahabadi (2019)
The conventional, linear, take-make-waste economy which was a by-product of the industrial revolution is not a viable option anymore. Environmental concerns are driving the development of a new circular model in which reduce, reuse, and recycle are key. Since this circular model would keep materials in commerce for longer, safer product designs that would reduce the amount of hazardous materials are vital. In this work, the aim is to implement this design philosophy in producing polymer/graphene nanocomposites as a rapidly emerging class of materials. The design philosophy is based on two strategies: first, to substitute conventional, synthetic components by their naturally-occurring counterparts and, second, by eliminating chemicals by assigning their roles to other multifunctional components.